POTENSI EKONOMI PENGEMBANGAN USAHA BUDIDAYA TAMBAK UDANG WINDU DI KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Erwan Sulistianto (Jurnal Harpodon Borneo, 2016)
The aim this research is to analyze the economic potential development of aquaculture in Muara Badak District. The data analysed use 4 methods, that are NPV, IRR, Net BCR, and Payback Period. The result showed that financially the business of shrimp culture in pond is feasible to be developed in the present and future, with NPV Rp 321.436.446,78, IRR 20%, NBCR 1,80 and Payback Period 62 mounth.Keywords : Shrimp culture, pond, economic potential